Intonation across two border areas in the North Andean region: Mérida (Venezuela) and Medellin (Colombia) (2020)
ABSTRACT: The Andes mountain system serves as a natural border throughout several South American countries. This research takes place in the region known as the Northern Andes, in two of the most important cities of the Venezuelan and Colombian Andes: Mérida, State of Mérida, and Medellin, Department of Antioquia. The main purpose of this study is to establish intonation similarities and differences between these two Andean cities. As a preliminary study, part of the AMPER Project, it examines the F0 as a melodic support. The study has been conducted according to the parameters established in the above- mentioned project. The intention of this research is twofold: First, to accomplish one of the main AMPER goals of performing comparative studies among diverse Romance languages and its varieties; and secondly, to establish possible relationships and differences among language varieties that are in contact, despite being separated by borderlines.